A Corpus-Based Analysis of Power Plant Engineering Textbooks: Lexical Patterns and Their Pedagogical Implications for English for Specific Purposes - Danu Angga Vebriyanto; Eri Prihatmini; Filda Hulwani Dewi; Diah Wulansari Hudaya; Rangga Permana (Teaching and Learning Research Journal, 2026)
Power Plant Engineering textbooks play a vital role in supporting English for Specific Purposes (ESP) instruction; however, their lexical characteristics have received limited attention in corpus-based research. This study aims to identify the lexical patterns of Power Plant Engineering textbooks and examine their pedagogical implications for ESP. A specialized corpus was compiled from nine English-language textbooks and analyzed using AntConc version 4.3.1. The analysis focused on word frequency, collocations, lexical bundles, and concordance patterns. The findings revealed that the corpus is characterized by a high frequency of discipline-specific vocabulary, recurrent collocations, and formulaic lexical bundles that reflect the distinctive features of Power Plant Engineering discourse. These lexical patterns indicate that technical knowledge is communicated through stable phraseological units rather than isolated words. The findings provide an empirical basis for developing discipline-specific vocabulary lists, corpus-informed teaching materials, and ESP curricula. This study demonstrates that corpus analysis is an effective approach for identifying authentic engineering language and supporting evidence-based ESP instruction.